A Rapamycin-Sensitive Signaling Pathway Is Essential for the Full Expression of Persistent Pain States - Geranton, Sandrine M; Jimenez-Diaz, Lydia; Torsney, Carole; Tochiki, Keri K; Stuart, Sarah A; Leith, J. Lianne; Lumb, Bridget M; Hunt, Stephen P (The Journal of neuroscience, 2009)
Translational control through the mammalian target of rapamycin (mTOR) is critical for synaptic plasticity, cell growth, and axon guidance. Recently, it was also shown that mTOR signaling was essential for the maintenance of the sensitivity of subsets of adult sensory neurons. Here, we show that persistent pain states, but not acute pain behavior, are substantially alleviated by centrally administered rapamycin, an inhibitor of the mTOR pathway. We demonstrate that rapamycin modulates nociception by acting on subsets of primary afferents and superficial dorsal horn neurons to reduce both primary afferent sensitivity and central plasticity. We found that the active form of mTOR is present in a subpopulation of myelinated dorsal root axons, but rarely in unmyelinated C-fibers, and heavily expressed in the dorsal horn by lamina I/III projection neurons that are known to mediate the induction and maintenance of pain states. Intrathecal injections of rapamycin inhibited the activation of downstream targets of mTOR in dorsal horn and dorsal roots and reduced the thermal sensitivity of A-fibers. Moreover, in vitro studies showed that rapamycin increased the electrical activation threshold of Aδ-fibers in dorsal roots. Together, our results imply that central rapamycin reduces neuropathic pain by acting both on an mTOR-positive subset of A-nociceptors and lamina I projection neurons and suggest a new pharmacological route for therapeutic intervention in persistent pain states.